Changes in rocket salad phytochemicals within the commercial supply chain: Glucosinolates, isothiocyanates, amino acids and bacterial load increase significantly after processing. (15th April 2017) - Bell, Luke; Yahya, Hanis Nadia; Oloyede, Omobolanle Oluwadamilola; Methven, Lisa; Wagstaff, Carol
Highlights: Glucosinolates, isothiocyanates and amino acids increase significantly over time. Glucoraphanin is not significantly affected by harvesting and processing. Sulforaphane significantly increases after processing in E. sativa cultivars. Bacterial load of leaves is correlated with glucosinolate and amino acid abundance. Commercial processing may increase the nutritional value of E. sativa to consumers. Abstract: Five cultivars of Eruca sativa and a commercial variety of Diplotaxis tenuifolia were grown in the UK (summer) and subjected to commercial growth, harvesting and processing, with subsequent shelf life storage. Glucosinolates (GSL), isothiocyanates (ITC), amino acids (AA), free sugars, and bacterial loads were analysed throughout the supply chain to determine the effects on phytochemical compositions. Bacterial load of leaves increased significantly over time and peaked during shelf life storage. Significant correlations were observed with GSL and AA concentrations, suggesting a previously unknown relationship between plants and endemic leaf bacteria. GSLs, ITCs and AAs increased significantly after processing and during shelf life. The supply chain did not significantly affect glucoraphanin concentrations, and its ITC sulforaphane significantly increased during shelf life in E. sativa cultivars. We hypothesise that commercial processing may increase the nutritional value of the crop, and have added health benefits for the consumer.